Advanced medical technologies used in monitoring and therapy for diabetes - review work - Anna Katarzyna Taracha; Anna Katarzyna Orzeł; Zuzanna Toruń; Barbara Zofia Klatka; Magdalena Majcher; Marcin Lewicki (Kazimierz Wielki University, 2019)
Throughout the years monitoring and therapy of diabetes was significantly changing. Undoubtedly, a definite improvement of applied technologies not only increased the average life expectancy of diabetic patients but also influenced their comfort. The purpose of the study was to present the history of methods diagnosis and treatment of diabetes. Additionally, promising modern medical technologies were reviewed. Nanotechnology, modern robots and transplants of pancreatic islets are currently under experiments showing satisfactory results. These technologies enable monitoring of glucose level, prevent hypoglycemia and sustain normoglycemia. Moreover, surgical attempt involving transplantation give a chance to counter the complications followed by diabetes development.